Area Problem I

Geometry Level 3

In A B C \triangle ABC as shown above, C = 9 0 \angle C=90^\circ , A D AD and B E BE , which intersect at I I , are bisectors of B A C \angle{BAC} and A B C \angle{ABC} respectively. If the area of I A B \triangle IAB is 6 6 , find the area of quadrilateral A B D E . ABDE.


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

David Vreken
Aug 19, 2019

Let a = B C a = BC , b = A C b = AC , and c = A B c = AB . Since A B C \triangle ABC is a right triangle, a 2 + b 2 = c 2 a^2 + b^2 = c^2 , and since I I is at the intersection of the angle bisectors of A B C \triangle ABC , it is the incenter of A B C \triangle ABC with an incircle radius of r = a b a + b + c r = \frac{ab}{a + b + c} . The area of I A B \triangle IAB is then A I A B = 1 2 c r = a b c 2 ( a + b + c ) A_{\triangle IAB} = \frac{1}{2}cr = \frac{abc}{2(a + b + c)} .

Now place and rotate the diagram on a coordinate graph so that C C is on the origin, A A is on the x x -axis, and B B is on the y y -axis.

Then the line through B ( 0 , a ) B(0, a) and I ( a b a + b + c , a b a + b + c ) I(\frac{ab}{a + b + c}, \frac{ab}{a + b + c}) has an equation of y = a + c a b x + a y = -\frac{a + c}{ab}x + a , so that E E is the x x -intercept at E ( a b a + c , 0 ) E(\frac{ab}{a + c}, 0) , which means C E = a b a + c CE = \frac{ab}{a + c} . By a similar argument, C D = a b b + c CD = \frac{ab}{b + c} .

The area of quadrilateral A B D E ABDE is A A B D E = A A B C A C D E = 1 2 a b 1 2 a b a + c a b b + c A_{ABDE} = A_{\triangle ABC} - A_{CDE} = \frac{1}{2}ab - \frac{1}{2}\frac{ab}{a + c}\frac{ab}{b + c} , which simplifies to A A B D E = a b c a + b + c = 2 A I A B A_{ABDE} = \frac{abc}{a + b + c} = 2A_{\triangle IAB} .

Since A I A B = 6 A_{\triangle IAB} = 6 , A A B D E = 2 6 = 12 A_{ABDE} = 2 \cdot 6 = \boxed{12} .

Chew-Seong Cheong
Aug 18, 2019

Let A = θ \angle A = \theta ; then B = 9 0 θ \angle B = 90^\circ - \theta , I A B = θ 2 \angle IAB = \dfrac \theta 2 and I B A = 4 5 θ \angle IBA = 45^\circ - \theta . Let A B = c AB=c and I F IF be perpendicular to A B AB with length r r . Then

c = r cot θ 2 + r cot ( 4 5 θ 2 ) Let t = tan θ 2 = r ( 1 t + 1 + t 1 t ) r = c t ( 1 t ) 1 + t 2 Since [ I A B ] = r c 2 = 6 r c = c 2 t ( 1 t ) 1 + t 2 = 12 \begin{aligned} c & = r \cot \frac \theta 2 + r \cot \left(45^\circ - \frac \theta 2 \right) & \small \color{#3D99F6} \text{Let }t = \tan \frac \theta 2 \\ & = r\left( \frac 1t + \frac {1+t}{1-t} \right) \\ \implies r & = \frac {ct(1-t)}{1+t^2} & \small \color{#3D99F6} \text{Since }[IAB] = \frac {rc}2 = 6 \\ rc & = \color{#3D99F6} \frac {c^2t(1-t)}{1+t^2} = 12 \end{aligned}

Now the area of A B C \triangle ABC ,

[ A B C ] = B C × A C 2 = c 2 2 sin θ cos θ = c 2 2 × 2 t 1 + t 2 × 1 t 2 1 + t 2 = c 2 t ( 1 t ) ( 1 + t ) ( 1 + t 2 ) ( 1 + t 2 ) Recall c 2 t ( 1 t ) 1 + t 2 = 12 = 12 ( 1 + t ) 1 + t 2 \begin{aligned} [ABC] & = \frac {\overline{BC} \times \overline{AC}}2 \\ & = \frac {c^2}2 \sin \theta \cos \theta \\ & = \frac {c^2}2 \times \frac {2t}{1+t^2} \times \frac {1-t^2}{1+t^2} \\ & = \frac {{\color{#3D99F6}c^2t(1-t)}(1+t)}{{\color{#3D99F6}(1+t^2)} (1+t^2)} & \small \color{#3D99F6} \text{Recall } \frac {c^2t(1-t)}{1+t^2} = 12 \\ & = \frac {{\color{#3D99F6}12}(1+t)}{1+t^2} \end{aligned}

And the area of C D E \triangle CDE .

[ C D E ] = C D × C E 2 = A C tan θ 2 × B C tan ( 4 5 θ 2 ) 2 = c 2 2 sin θ cos θ tan θ 2 tan ( 4 5 θ 2 ) Recall c 2 2 sin θ cos θ = 12 ( 1 + t ) 1 + t 2 = 12 ( 1 + t ) 1 + t 2 × t ( 1 t ) 1 + t \begin{aligned} [CDE] & = \frac {\overline{CD} \times \overline{CE}}2 \\ & = \frac {\overline{AC} \tan \frac \theta 2 \times \overline{BC} \tan \left(45^\circ - \frac \theta 2\right)} 2 \\ & = {\color{#3D99F6}\frac {c^2}2 \sin \theta \cos \theta} \tan \frac \theta 2 \tan \left(45^\circ - \frac \theta 2\right) & \small \color{#3D99F6} \text{Recall } \frac {c^2}2 \sin \theta \cos \theta = \frac {12(1+t)}{1+t^2} \\ & = {\color{#3D99F6} \frac {12(1+t)}{1+t^2}} \times \frac {t(1-t)}{1+t} \end{aligned}

Therefore, the area of quadrilateral A B D E ABDE ,

[ A B D E ] = [ A B C ] [ C D E ] = 12 ( 1 + t ) 1 + t 2 ( 1 t ( 1 t ) 1 + t ) = 12 ( 1 + t ) 1 + t 2 ( 1 + t 2 1 + t ) = 12 \begin{aligned} [ABDE] & = [ABC] - [CDE] \\ & = \frac {12(1+t)}{1+t^2} \left(1- \frac {t(1-t)}{1+t}\right) \\ & = \frac {12(1+t)}{1+t^2} \left(\frac {1+t^2}{1+t}\right) \\ & = \boxed{12} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...